Silica Adsorption from Boiler Effluent Using Activated Charcoal Derived from Palm Oil Fibre Waste with H3PO4 Activator - Ricky Fernando; Shintawati Shintawati; Livia Rhea Alvita; Yeni Ria Wulandari; Adityas Agung Ramandani; Febrina Arief (Universitas PGRI Madiun, 2024)
Most waste from palm oil processing can be repurposed, such as using palm fibre waste to create activated charcoal. This study aimed to assess the effectiveness of activated charcoal, produced by activating palm fibre with H?PO?, in removing silica from boiler output water. The production process involved pyrolysis at 200ºC for 2.5 hours. A completely randomized design was employed to test the effects of different H?PO? concentration (with 1 to 2 M) and reaction times (30, 60, and 90 min). Results revealed that the moisture content of the activated charcoal ranged from 1.96% to 2.42%, ash content from 9.82% to 21.63%, and iodine adsorption from 366.43 to 457.87 mg/g. The highest silica adsorption capacity (3.5 g/g) was achieved with 2 M H?PO? for 90 min. This indicates that palm fibre-derived activated charcoal is effective for silica removal, highlighting it is potential for enhancing environmental sustainability in industrial sector.